Traditional Cardiovascular risk-factors among healthcare workers in Kelantan, Malaysia - Hazmi, Helmy; Wan Rosli, W. I.; Abd Jalil, Rohana; Gan, Siew Hua; Hamid, Noor Fadzlina; Harun, Rosliza; Shafei,, Mohd Nazri; Ibrahim, Mohd Ismail; Wan Bebakar, Wan Mohamad; Ismail, Shaiful Bahri; Musa, Kamarul Imran (SEAMEO TROPMED Network, 2015)
We conducted a cross sectional study of cardiovascular risk factors among healthcare workers at four government hospitals in Kelantan, Malaysia. We randomly selected 330 subjects fulfilling the following study criteria: those who had been working for at least one year at that health facility, Malaysians citizens and those with some form of direct contact with patients. We conducted an interview, obtained physical measurements, a fasting blood sugar and fasting lipid profiles among 308 subjects. The mean age of the subjects was 43.5 years, 82% were female; 30.8%, 14.3%, 10.4%, 1.3% and 1.6% of the subjects had dyslipidemia, hypertension, diabetes mellitus, a history of stroke and a history of ischemic heart disease, respectively. Forty-two percent of subjects had at least one medical condition. The mean body mass index (BMI) was 27.0 kg/m2 (SD=4.8) and 24.3% haM BMI >30 kg/m2. The mean systolic and diastolic blood pressures were 121.5 mmHg (SD=14.0) and 76.5 mmHg (SD=9.7), respectively and the mean waist-hip ratio was 0.84 (SD=O.I). The mean fasting blood sugar, total cholesterol, triglyceride, high density lipoprotein and low density lipoprotein were 5.8 mmol/l (SD=2.4), 5.5 mmol/l (SD=1.0), 1.4 mmol/l (SD=0.9), 1.5 mmol/l (SD=0.3) and 3.5 mmol/l (SD=0.9), respectively. Our study population had a smaller proportion of hypertension than that of the general Malaysian population. They had higher fasting total cholesterol, slightly lower fasting blood sugar, with a large proportion of them, obese and had diabetes. Immediate intervention is needed to reduce the traditional cardiovascular risk factors in this population.